Demonstrações do Teorema da Amizade - Rogério Santana Calegari (2018)
This paper aims to present two demonstrations of the theorem, known in Mathematics, as Friendship Theorem, being stated in this way: In a meeting with n people, where both have exactly one common friend, there is someone in the meeting who knows all the people. We begin the work with some definitions related to Discrete Mathematics, Linear Algebra and Graph Theory. Next, we present a timeline about demonstrations of the theorem in the last decades, with information obtained through digital channel search. We conclude the work by presenting the two demonstrations of the Theory of Friendship, the first using contents of Graph Theory and Linear Algebra and the second by Combinatorial Analysis